2016
DOI: 10.1038/srep34713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Experimental Direct Pulp-capping Material on the Properties and Osteogenic Differentiation of Human Dental Pulp Stem Cells

Abstract: Effective pulp-capping materials must have antibacterial properties and induce dentin bridge formation; however, many current materials do not satisfy clinical requirements. Accordingly, the effects of an experiment pulp-capping material (Exp) composed of an antibacterial resin monomer (MAE-DB) and Portland cement (PC) on the viability, adhesion, migration, and differentiation of human dental pulp stem cells (hDPSCs) were examined. Based on a Cell Counting Kit-8 assay, hDPSCs exposed to Exp extracts showed lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Another crucial finding was in relation to the migration rate and cell adherence enhancement observed in the miR-143-5p inhibitors group. This finding was in concert with that of a previously conducted study, which demonstrated that a new direct pulp-capping material containing an antibacterial resin monomer as well as Portland cement could potentially enhance the adhesion and migration of DPSCs [Yu et al, 2016]. A demineralized dentin matrix has displayed its ability in enhancing DPSC adhesion and migration [Liu et al, 2016].…”
Section: Discussionsupporting
confidence: 77%
“…Another crucial finding was in relation to the migration rate and cell adherence enhancement observed in the miR-143-5p inhibitors group. This finding was in concert with that of a previously conducted study, which demonstrated that a new direct pulp-capping material containing an antibacterial resin monomer as well as Portland cement could potentially enhance the adhesion and migration of DPSCs [Yu et al, 2016]. A demineralized dentin matrix has displayed its ability in enhancing DPSC adhesion and migration [Liu et al, 2016].…”
Section: Discussionsupporting
confidence: 77%
“…This study aimed at developing a light-curable material for pulp capping with potential antibacterial properties and potential ability to induce mineralized tissue formation. In previous studies, this material retained contact inhibition antibacterial activity for at least 6 months (Yang et al 2014) and had excellent biocompatibility (Yu et al 2016). In the present study, the basic properties of the material were investigated and compared with two commercial pulp capping materials.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, a high DC can improve biocompatibility, which has been demonstrated in a previous study (Yu et al . ), because less unreacted monomers are able to leach into the surrounding tissues and cause an inflammatory reaction (Gandolfi et al . , Mehdawi et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations